Peran Workshop Digital Marketing dalam Pemberdayaan Kaum Perempuan Untuk Meningkatkan Ekonomi Keluarga di Desa Paya Angus: Penelitian - Selpi Saputri; Annisa Kiara Rigi; Mela Diana; Echa Avira; Akhmad Syarifullah; Oka Suci Wulandari; Abila Kaisa Salpa; Imam Warmansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study explores the role of digital marketing workshops in empowering women to enhance family economy in Paya Angus Village, where digital transformation offers opportunities for rural micro-enterprises despite low literacy barriers. The main objective is to analyze the workshop's impact on women's knowledge, skills, and income. Employing a descriptive qualitative approach during KKN from January to February 2026, the population consists of female workshop participants (housewives and MSME actors), with data collection via in-depth interviews, observations, and documentation; analysis conducted thematically and iteratively. Findings reveal improved digital literacy, online marketing skills, stable income growth, and economic independence, hindered by internet infrastructure limitations. The conclusion affirms the workshop as an effective sustainable empowerment model via multi-stakeholder collaboration.